2017
DOI: 10.1007/s11523-017-0515-4
|View full text |Cite
|
Sign up to set email alerts
|

EGFR Mutation Testing of non-squamous NSCLC: Impact and Uptake during Implementation of Testing Guidelines in a Population-Based Registry Cohort from Northern New Zealand

Abstract: In this real world setting, high uptake of EGFR testing was achieved and associated with major changes in EGFR-TKI prescribing and improved health outcomes. Modifiable factors determined testing uptake. Study registration ACTRN12615000998549.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 52 publications
1
25
1
Order By: Relevance
“…In 2010, the EGFR testing rate for NSCLC patients was 16.8% in the United States, compared to 63.5% in Korea . In 2012, a Swedish study reported that 49% of advanced NSCLC patients were tested for the EGFR gene, while a 2014 study conducted in New Zealand revealed the EGFR testing rate to be 67% . As EGFR mutations are more common in Asian compared to Western patients, EGFR molecular testing in Chinese patients is important.…”
Section: Introductionmentioning
confidence: 99%
“…In 2010, the EGFR testing rate for NSCLC patients was 16.8% in the United States, compared to 63.5% in Korea . In 2012, a Swedish study reported that 49% of advanced NSCLC patients were tested for the EGFR gene, while a 2014 study conducted in New Zealand revealed the EGFR testing rate to be 67% . As EGFR mutations are more common in Asian compared to Western patients, EGFR molecular testing in Chinese patients is important.…”
Section: Introductionmentioning
confidence: 99%
“…Although the proportion of patients with ALK‐positive NSCLC is relatively modest, there is still a substantial number of ALK‐positive patients likely to present each year who will benefit from treatment with ALK TKI. Each year in New Zealand, approximately 1200 patients are diagnosed with non‐squamous NSCLC, so it is likely that about 50 to 100 of these individuals will have ALK‐positive disease.…”
Section: Discussionmentioning
confidence: 99%
“…The study was approved by the Northern Health and Disability Ethics committee (No: 13/NTB/165/AM02) and registered (ACTRN12615000998549). More details about the study design and setting are described elsewhere …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations